Euphorbia zhongiana (Euphorbia section Helioscopia, subgenus Esula, Euphorbiaceae), a new species from Danxia Landform Areas in Zhejiang Province, Eastern China - Li, Jun-Ping; Xu, Pan; Chen, Feng; Pu, Jin-Bao; Xie, Wen-Yuan; Wang, Jun-Feng; Wang, Jian-Sheng; Zhu, Hua-Min; Chen, Zheng-Hai; Liang, Wei-Qing (Phytotaxa, 2024)
Euphorbia zhongiana (Euphorbiaceae), from Zhejiang Province, eastern China, is described and illustrated as a new species. It is morphologically similar to E. fauriei, however, differs in its winter green habit, whole plant being glabrous; cyathophylls 2, broadly ovate, yellow-greenish; involucre 2.5–3.0 × 2.5–3.0 mm; the surface of ovary usually smooth, rare sparsely microtuberous; styles connate at middle towards base; apex slightly 2–lobed; capsules smooth without tuberculate or conical verrucae, rare sparsely and inconspicuously rugose; seed coat with reticulate wrinkle.